2022
DOI: 10.3390/ijerph19127447
|View full text |Cite
|
Sign up to set email alerts
|

Voronoi Diagrams for Senior-Friendly Cities

Abstract: Motives: Active aging places (AAP) should be identified during the COVID-19 pandemic to ensure the sanitary safety of seniors, prevent older adults from feeling excluded, and eliminate health threats that discourage seniors from being active. Aim: The aim of this study was to apply a new analytical approach with the use of Voronoi diagrams in GIS tools to spatially identify the AAP in the context of apparent social dynamics. Methods: An empirical study was conducted with the use of qualitative (literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The adopted methodology was based on a review of the literature, including Statistics Poland and Eurostat data (social and economic factors), and the results of a questionnaire survey. The survey questionnaire was developed by members of the research team who relied on their expert knowledge as investigators in a research project based on the results of previous studies examining older people's activity levels (Dawidowicz et al, 2020;Figurska et al, 2022), urban landscape components (Senetra et al, 2015), and the functional and spatial indicators of residential estates in cities (Dawidowicz & Dudzińska, 2022). The results were processed statistically in a comparative analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adopted methodology was based on a review of the literature, including Statistics Poland and Eurostat data (social and economic factors), and the results of a questionnaire survey. The survey questionnaire was developed by members of the research team who relied on their expert knowledge as investigators in a research project based on the results of previous studies examining older people's activity levels (Dawidowicz et al, 2020;Figurska et al, 2022), urban landscape components (Senetra et al, 2015), and the functional and spatial indicators of residential estates in cities (Dawidowicz & Dudzińska, 2022). The results were processed statistically in a comparative analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, a 2019 study revealed that a growing number of Polish older persons remain professionally active, enrol in educational programs, and pursue active recreational interests (Dawidowicz et al, 2020). 44% of retired adults remain professionally active (Figurska et al, 2022). Older people value independent living, but the COVID-19 pandemic significantly decreased activity levels of older people (Zych, 2020).…”
Section: Lifestyle and Sense Of Security Of Older People In Polandmentioning
confidence: 99%
See 1 more Smart Citation
“…In the classical Voronoi diagram, the cells have the following mathematical meaning: any point of the Voronoi cell is closest to the centroid based on which the cell was built ( Figure 16 ). Each cell can be considered a zone of influence of an atom or other object, played by a point [ 52 , 53 , 54 , 55 ].…”
Section: Alternative Modelsmentioning
confidence: 99%
“…The method assumes an optimal distance of 500 m to a water body, acceptable across various age groups of the respondents. This distance is one that seniors can comfortably cover on foot [28,51].…”
Section: Research Frameworkmentioning
confidence: 99%